Interface issues of lithium metal anode for high‐energy batteries: Challenges, strategies, and perspectives. Issue 2 (15th January 2021) - Han, Yiyao; Liu, Bo; Xiao, Zhen; Zhang, Wenkui; Wang, Xiuli; Pan, Guoxiang; Xia, Yang; Xia, Xinhui; Tu, Jiangping
Abstract: Lithium (Li) metal is considered as one of the most promising anode materials for next‐generation high‐energy‐density storage systems. However, the practical application of Li metal anode is hindered by interfacial instability and air instability due to the highly reactivity of Li metal. Unstable interface in Li metal batteries (LMBs) directly dictates Li dendrite growth, "dead Li" and low Coulombic efficiency, resulting in inferior electrochemical performance of LMBs and even safety issues. In addition, its sensitivity to ambient air leads to the severe corrosion of Li metal anode, high requirements of production and storage, and increased manufacturing cost. Plenty of efforts in recent years have overcome many bottlenecks in these fields and hastened the practical applications of high‐energy‐density LMBs. In this review, we focus on emerging methods of these two aspects to fulfill a stable and low cost electrode. In this perspective, design artificial solid electrolyte interphase (SEI) layers, construct three‐dimensional conductive current collectors, optimize electrolytes, employ solid‐state electrolytes, and modify separators are summarized to be propitious to ameliorate interfacial stability. Meanwhile, ex situ/in situ formed protective layers are highlighted in favor of heightening air stability. Finally, several possible directions for the future research on advanced Li metal anode are addressed. Abstract : In this review, we summarize the feasible strategies of ameliorating interfacial stability and air stability of lithium metal anode to make it more suitable for practical applications in high‐energy‐density storage systems. Meanwhile, we propose the challenges and perspectives for the future research of lithium metal anode in high‐energy batteries.